Convergence of Chorin-Marsden Formula for the Navier-Stokes Equations on Convex Domains (Journal of Computational Mathematics, 1999)
We prove the convergence of the Chorin-Marsden product formula for solving the initial-boundary value problems of the Navier-Stokes equations on convex domains. As a particular case we consider the case of the half plane.